Pengembangan Modul Digital IPA Berbasis Contextual Teaching and Learning (CTL) untuk Siswa Kelas IV Sekolah Dasar - Putra, Lovandri Dwanda; Sentia, Eti (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Implementing information technology is an effective, efficient way of conveying information in learning. The selection of digital modules as learning media is closely related to the rapid development of technology. The development of this digital module media is that the learning media available in schools have not varied, and digital modules based on Contextual Teaching and Learning (CTL) on style material have yet to be developed. The purposes of this study are as follows: (1) to develop digital media modules based on Contextual Teaching and Learning (CTL) in science learning style material for fourth-grade elementary school students (2) to find out the quality and feasibility of digital media modules based on Contextual Teaching and Learning (CTL) in science learning style material for fourth-grade elementary school students. This study belongs to the research and development (R&D) type by using the ADDIE development method. The data collection technique uses a questionnaire on the assessment results of expert validators, educators and students. Data analysis techniques using qualitative analysis techniques are carried out by describing the data obtained from criticism, suggestions, input and comments and quantitative data obtained from the results of the assessment sheet. The respondents referred to educators and students. The trial was conducted on students first explaining digital modules based on Contextual Teaching and Learning (CTL) in science learning style material. Students could try out these digital modules. The results of the assessment of the quality of digital module media by media experts scored 92 "very good", material experts scored 86.6 "very good", learning experts scored 94.6 "very good," and linguists scored 78.6 " Good ". This digital module is very feasible to be used as teaching material for students.